"They Shouldn't Be Coming to the ED, Should They?": A Descriptive Service Evaluation of Why Patients With Palliative Care Needs Present to the Emergency Department. (December 2017) - Green, Emilie; Ward, Sarah; Brierley, Will; Riley, Ben; Sattar, Henna; Harris, Tim
Background: Patients with palliative care needs frequently attend the emergency department (ED). There is no international agreement on which patients are best cared for in the ED, compared to the primary care setting or direct admission to the hospital. This article presents the quantitative phase of a mixed-methods service evaluation, exploring the reasons why patients with palliative care needs present to the ED. Methods: This is a single-center, observational study including all patients under the care of a specialist palliative care team who presented to the ED over a 10-week period. Demographic and clinical data were collected from electronic health records. Results: A total of 105 patients made 112 presentations to the ED. The 2 most common presenting complaints were shortness of breath (35%) and pain (28%). Eighty-three percent of presentations required care in the ED according to a priori defined criteria. They either underwent urgent investigation or received immediate interventions that could not be delivered in another setting, were referred by a health-care professional, or were admitted. Conclusions: Findings challenge the misconception that patients known to a palliative care team should be cared for outside the ED. The importance and necessity of the ED for patients in their last years of life has been highlighted, specifically in terms of managing acute, unpredictable crises. Future service provision should not be based solely on a patient's presenting complaint. Further qualitative research exploring patient perspective is required in order to explore the decision-making process that leads patients with palliative care needs to the ED.